O deficiente e o mercado de trabalho: uma análise dos programas de qualificação profissional no município de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
In the contemporaneous world, the labor market is in constant transformation due to the inclusion of new technologies and forms of organization of the productive process, which demands from the worker the development of skills that will enable their permanence in the job before a competitive scenario. In the case of workers with disability, remain inserted in the labor market is even more difficult due to several factors, whether of social, economic and even cultural order, that’s why the qualification represents a fundamental weapon for this group, as a way to make effective their inclusion both professional and social. Given the above, the present dissertation aims to analyze the social contribution of professional qualification programs for people with disability in the city of Manaus, with emphasis on the preparing of this group for the labor market. It still has as specific objectives, understand the fundamental aspects of disability through concepts, terminologies and models; know the historical and social evolution of people with disability; understand the work world and labor laws, especially those governing the National Policy for the Integration of People with Disability; and verify, at the municipal level, the dynamics of the labor market and the working process of professional qualification programs for people with disability. For the research, were chosen two professional qualification programs developed in Manaus: the Curupira Project, from the Federal Institute of Education, Science and Technology of Amazon (IFAM), and the Program SENAI of Inclusive Actions, this one in period from 2012 to 2014. The research was based on quantitative and qualitative approach, of descriptive, bibliographical and documentary character, because were used theoretical references and internal documents related to the operation of the programs. The research method used was dialectical, because the aim was to understand the dynamics of the programs, from the relationship these establish with the other spheres of society. The field study was conducted through questionnaires, with the participation of students and coordinators, as well as documentary study in loco with the help of employees who work in the programs. The results allowed concluding that in some cases the programs' social contribution goes beyond offering the qualification for the job, as it contributes to the development of the autonomy and independence of the individual. In such cases, it was observed that the inclusion in the labor market is carried out effectively, bringing life improvements to these workers with disability.
Keywords: Pessoa com Deficiência; Mercado de Trabalho; Qualificação Profissional; Person with Disability; Labor Market; Professional Qualification; CIÊNCIAS HUMANAS: SOCIOLOGIA